2014
DOI: 10.12659/msm.891103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Therapy of Periosteum and Bone Allograft in a Critical-Sized Defect Model in New Zealand White Rabbits

Abstract: BackgroundLarge segmental bone defects caused by trauma, infection, or bone tumor resection are difficult to cure and have been a problem in the field of bone repair for decades. The objective of this study was to discuss the efficacy of combined therapy of free periosteum and bone allograft in treating bone defects and to provide a theoretical basis for clinical application of this therapy.Material/MethodsA unilateral tibia cortical defect model in New Zealand white rabbits was established according to Girola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…ii) Reparative phase (callus formation), in areas closer to the well-vascularized healthy bone tissue, osteogenic cells differentiate into osteoblasts, which produce spongy bone trabeculae, this stage lasts ~4-8 weeks. iii) Remodeling phase, this is the final phase of healing, where compact bone replaces spongy bone around the periphery of the fracture site, this stage lasts ~8-12 weeks ( 23 ). Therefore, 4, 8 and 12 weeks were chosen as the time points assessed in the present study; this is consistent with other studies ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ii) Reparative phase (callus formation), in areas closer to the well-vascularized healthy bone tissue, osteogenic cells differentiate into osteoblasts, which produce spongy bone trabeculae, this stage lasts ~4-8 weeks. iii) Remodeling phase, this is the final phase of healing, where compact bone replaces spongy bone around the periphery of the fracture site, this stage lasts ~8-12 weeks ( 23 ). Therefore, 4, 8 and 12 weeks were chosen as the time points assessed in the present study; this is consistent with other studies ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…An X-ray device (45 kV, 100 mA, 0.12 sec; Siemens 1350; Siemens AG) was used to investigate the bone-healing process. X-ray scoring was performed according to the Lane-Sandhu standards ( Table I ) ( 23 ), including bone connection, recanalization of the medullary cavity and bone formation in the bone defect area, which were scored by three independent examiners. The images were captured three per group at three time points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone allograft is usually used to replace bone defects due to its size and shape, but it usually resulted in junctional nonunion and bone fracture (88). The utilisation of periosteal transplantation on allograft surgery have been reported in several experimental and clinical studies (53,(89)(90)(91). Karaoglu et al (89) demonstrated that demineralized deep-frozen allograft covered with non-vascularised periosteum resulted in rapid and high quality ossification it was reported that bone allograft wrapped with non-vascularised periosteal graft have similar efficacy with standard treatment using autogenous bone graft transfer for the repair of bone defects in rabbits (90).…”
Section: Usage Of Periosteum Transplant On Bone Allograft Surgerymentioning
confidence: 99%
“…The utilisation of periosteal transplantation on allograft surgery have been reported in several experimental and clinical studies (53,(89)(90)(91). Karaoglu et al (89) demonstrated that demineralized deep-frozen allograft covered with non-vascularised periosteum resulted in rapid and high quality ossification it was reported that bone allograft wrapped with non-vascularised periosteal graft have similar efficacy with standard treatment using autogenous bone graft transfer for the repair of bone defects in rabbits (90). Likewise, a study by Santić et al (57) revealed better bone healing in tibial defect of rabbits that were treated with allogenous bone graft covered with vascularised periosteal graft, compared to their counterparts that received allogenous bone graft with non-vascularised periosteal graft (85).…”
Section: Usage Of Periosteum Transplant On Bone Allograft Surgerymentioning
confidence: 99%